(3GdGZJHGW HeYQaI ef Qei HGdGNJdGWs - (3EHQGgje Hf eMeO Hf Ndjd GdnqWnQGoHodSj Ke GdMdHj, CHh GdhaGA, HQgGf GdOjf, pSrHW GHf GdnYnLej , J (B841 (3g` s ((3eMeO Hf CMeO Hf TeS GdMdHi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf GdN s
(3BNQgG (B:s
(3gPG BNQ GdeDda , hgh bGHd ddRjGOI aef hba Ydi CMOce jPcQg adjdMbg ai ecGfg s
(3hbO PcQ ajg ef NdW ai BNQ YeQg ef GdKbGJ hZjQges
(3hQJHg Ydi MQha GdeYLes
(3YdjgG NW GdeDda HbQGAJgG Ydjgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs